2011
DOI: 10.1071/fp09189
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying physiological determinants of genetic variation for yield potential in sunflower. SUNFLO: a model-based analysis

Abstract: Present work focussed on improving the description of organogenesis, morphogenesis and metabolism in a biophysical plant model (SUNFLO) applied to sunflower (Helianthus annuus L.). This first version of the model is designed for potential growth conditions without any abiotic or biotic stresses. Agreenhouse experiment was conducted to identify and estimate the phenotypic traits involved in plant productivity variability of 26 sunflower genotypes. The ability of SUNFLO to discriminate the genotypes was tested o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 41 publications
0
62
0
Order By: Relevance
“…The biomass partitioning module is an entirely new module. We describe here equations of these modules, briefly for those inherited from SUNFLO -we refer to Casadebaig et al (2011) and Lecoeur et al (2011) for an exhaustive description -and in detail for the new contributions. Model parameters that are mentioned in the following equations will be summarized in Section 2.3.…”
Section: Modeling: Sunlab Modulesmentioning
confidence: 99%
See 2 more Smart Citations
“…The biomass partitioning module is an entirely new module. We describe here equations of these modules, briefly for those inherited from SUNFLO -we refer to Casadebaig et al (2011) and Lecoeur et al (2011) for an exhaustive description -and in detail for the new contributions. Model parameters that are mentioned in the following equations will be summarized in Section 2.3.…”
Section: Modeling: Sunlab Modulesmentioning
confidence: 99%
“…Although this statistical solution and the large datasets used for its parameterization conferred good robustness to the prediction of HI and thereby crop harvest, biomass partitioning to other plant organs and trophic competition between organs were not taken into account. Moreover, it was shown in Lecoeur et al (2011) that HI is the parameter that contributes the most (14.3%) to the coefficient of variation of the potential grain yield. It was also shown that when ranking the processes in terms of their impact on yield variability, the first one was biomass allocation (before light interception according to plant architecture, plant phenology and photosynthesis).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The platform is currently developed and used in the laboratory of Applied Mathematics and Systems at Ecole Centrale Paris, but is also tested by a few other labs. Provided some basic knowledge in C++, it is very easy to implement models and to use the proposed methods: approximately 20 models of plant growth in interaction with the environment and variants are currently implemented in the platform: mostly in the GreenLab family [21] and variants of the STICS [6], CERES [32], SUNFLO [40] models, for different species. As such, it provides an interesting tool in the process of model comparison and benchmarking in the plant growth community as illustrated in [2].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the use of genotype specific parameters in models can only be of interest if we are able to determine significantly different parameter values for different genotypes [2]. However, most parameters cannot be measured directly or experimental protocols are heavy to implement [3] which indicate delicate parametrization. Consequently, some parameters have to be estimated from experimental data by model inversion.…”
Section: Introductionmentioning
confidence: 99%